Zeolite-templated carbon synthesized with ion-exchanged FAU-zeolite using alkaline earth metal ions for the selective adsorption of C2 hydrocarbons over C1 hydrocarbon - Kim, Ki Jun; Yoo, Chung Yul; Park, Joonhyeok; Lee, Yongjin; Cho, Churl hee; Cho, Dong Woo (Separation and Purification Technology, 2025)
In this study, zeolite-templated carbon (ZTC) was synthesized using ion-exchanged faujasite-Y (FAU, NaY) zeolites with different alkali earth metals (Mg2+, Ca2+, Sr2+, and Ba2+) to investigate the effects of these metals on the synthesis, characteristics, and C2/C1 hydrocarbon separation performance of ZTC. Thermogravimetric and temperature-programmed desorption of NH3 (TPD-NH3) analyses showed that carbon deposition tends to occur outside the pores because of the increasing number of moderate acid sites as the atomic number increases. In particular, in the case of FAU-ZTC(Ca) synthesized using CaY as the ZTC template, carbon accumulated inside the pores owing to the distribution of the appropriate acid strength, resulting in the highest specific surface area of 2,835 m2/g among the synthesized ZTCs. The combined X-ray photoelectron and Raman spectroscopy results confirm that these defect sites of ZTC act as adsorption sites for large molecules such as C2H4 and C2H6. The isothermal adsorption of CH4, C2H4, and C2H6 showed that FAU-ZTC(Ca) exhibited the highest adsorption capacity ratios of C2H4 and C2H6 to CH4, with a C2H6/CH4 ratio of 5.897 and C2H4/CH4 ratio of 5.288, respectively. The effective pore size ranges affecting the adsorption of CH4, C2H4, and C2H6 determined using linear regression analysis are 0.4 to 0.6 nm for CH4 and 0.6 to 1.1 nm for C2H4 and C2H6. Molecular simulations confirmed that the adsorption energy was maximized by the interaction between the hydrogen atoms of the hydrocarbons and the carbon atoms of ZTC. Furthermore, C2H4 and C2H6 require larger pores than CH4 adsorption because C2H4 and C2H6 prefer to lie horizontally rather than vertically in the pores of the ZTC.
Keywords: C2H4; C2H6; CH 4; FAU zeolites; Microporous carbons; Ordered microporous carbon; Pressure swing adsorption; Synthesised; Zeolite templated carbon; Zeolite templated carbons; C2H4; C2H6; CH4; Ordered microporous carbon; Pressure swing adsorption; Zeolite templated carbon (ZTC)